Shakespeare and the remains of Richard III - Schwyzer, Philip (Oxford University Press, 2013)
"This book explores how recollections and traces of the reign of Richard III survived a century and more to influence the world and work of William Shakespeare. In Richard III, Shakespeare depicts an era that had only recently passed beyond the horizon of living memory. The years between Shakespeare's birth in 1564 and the composition of the play in the early 1590s would have seen the deaths of the last witnesses to Richard's reign. Yet even after the extinction of memory, traces of the Yorkist era abounded in Elizabethan England - traces in the forms of material artefacts and buildings, popular traditions, textual records, and administrative and religious institutions and practices. Other traces had notoriously disappeared, not least the bodies of the princes reputedly murdered in the Tower, and the King's own body, which remained lost until its apparent rediscovery in the summer of 2012. Shakespeare and the Remains of Richard III charts the often complex careers of these pieces of the past over the course of a century framed on one side by the historical reign of Richard III (1483-85) and on the other by Shakespeare's play. Drawing on recent work in fields including archaeology, memory studies, and material biography, this book offers a fresh approach to the cultural history of the Tudor era, as well as a fundamentally new interpretation of the wellsprings and preoccupations of Richard III. The final emphasis is not only on what Shakespeare does with the traces of Richard's reign but also on what those traces do through Shakespeare--the play, in spite of its own pessimistic assumptions about history, has become the medium whereby certain fragments and remains of a long-lost world live on into the present day."--Publisher's description.